2018
DOI: 10.1016/j.rmed.2018.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide therapy is associated with lower mortality in community-acquired bacteraemic pneumonia

Abstract: In-hospital mortality, but not 30-day mortality, was significantly better in the macrolide group. Our data support the use of a macrolide in hospitalized patients with CAP and bacteraemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
(38 reference statements)
0
9
0
1
Order By: Relevance
“…A recent study has shown better outcomes in patients who received macrolide therapy and presented with bacteremic pneumonia. 34 Moreover, the most common cause of bacteremic pneumonia was pneumococcus in 74% of patients, and although the authors did not look at CRP levels, patients with invasive pneumococcal CAP usually presented greater levels of CRP. 35 A recent meta-analysis that compared the combination of a b-lactam with a macrolide vs a b-lactam with a fluoroquinolone showed no significant differences in short-term mortality (adjusted risk ratio, 1.26; 95% CI, 0.95-1.67; I 2 , 43%) 36 ; and another metaanalysis showed that ceftriaxone combination therapy was similar in terms of treatment success compared with fluoroquinolone monotherapy in patients with CAP.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study has shown better outcomes in patients who received macrolide therapy and presented with bacteremic pneumonia. 34 Moreover, the most common cause of bacteremic pneumonia was pneumococcus in 74% of patients, and although the authors did not look at CRP levels, patients with invasive pneumococcal CAP usually presented greater levels of CRP. 35 A recent meta-analysis that compared the combination of a b-lactam with a macrolide vs a b-lactam with a fluoroquinolone showed no significant differences in short-term mortality (adjusted risk ratio, 1.26; 95% CI, 0.95-1.67; I 2 , 43%) 36 ; and another metaanalysis showed that ceftriaxone combination therapy was similar in terms of treatment success compared with fluoroquinolone monotherapy in patients with CAP.…”
Section: Discussionmentioning
confidence: 98%
“…[ 38 , 39 ] The latter has been the rationale for including macrolides as part of the treatment regimen for SP infections even when resistance is demonstrated. [ 40 ] Additional investigations are warranted to verify our findings and to determine the optimal treatment approaches for SP infections. Developing new prevention strategies and treatment paradigms for SP infections is critical given the lack of mortality improvement with this infection over the past twenty years.…”
Section: Discussionmentioning
confidence: 79%
“…A recent study found lower in-hospital mortality in patients with bacteremic CAP who received a macrolide. 11 Although 95% of patients in both groups had adequate coverage for the identified pathogen, the lack of benefit of fluoroquinolones suggests that the macrolide benefit may be related to immunomodulatory activity rather than spectrum of activity. The emerging role for corticosteroids in PNA also indicates that immunomodulation may be beneficial.…”
Section: Discussionmentioning
confidence: 97%